1990
DOI: 10.1093/intimm/2.1.63
|View full text |Cite
|
Sign up to set email alerts
|

B—B cell interaction involved in polyclonal B cell activation is restricted by I-A but not by I-E molecules

Abstract: We have previously demonstrated that the class II MHC restricted B-B cell interaction is involved in the polyclonal differentiation of unprimed murine B cells into IgM-producing cells induced by a T cell-derived lymphokine B151-TRF2 or bacterial LPS. The present study has addressed the question of whether I-A and/or I-E molecules function as restriction elements for the B-B cell interaction. The results revealed that (B10 x B10.BR)F1(H-2b/k) B cells could be separated into I-Ab- and 1-Ak-restricted subpopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The I-E antigens ability to mediate allogeneic cooperation in vivo is in agreement with the full blown cGVHD induced through an isolated difference in I-E antigens [34,351. All these results are difficult to reconcile with the reported differential nature of the signals mediated by I-A and I-E molecules in the T-B interactions [25,26,36]. But, in agreement with the results presented in this report, it has been recently shown that the immune responses in I-A-I-E+ and in I-A+ I-E-mice are functionally equivalent [ 121.…”
Section: Discussionmentioning
confidence: 54%
“…The I-E antigens ability to mediate allogeneic cooperation in vivo is in agreement with the full blown cGVHD induced through an isolated difference in I-E antigens [34,351. All these results are difficult to reconcile with the reported differential nature of the signals mediated by I-A and I-E molecules in the T-B interactions [25,26,36]. But, in agreement with the results presented in this report, it has been recently shown that the immune responses in I-A-I-E+ and in I-A+ I-E-mice are functionally equivalent [ 121.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, mice which express E molecules are generally more susceptible to certain parasitic infections, provoking the speculation that a response restricted by this isotype can suppress the "clearing" response normally restricted by A molecules (8). Fourth and finally, there is some evidence that A and E molecules differentially mediate B cell interactions, perhaps because of variant signaling properties (9)(10)(11).…”
mentioning
confidence: 99%